Civil service reforms in Pakistan - Rana, Abdul Wajid (International Food Policy Research Institute, 2019)
Effective governance is one of the key challenges for both developing and developed countries. Governments, today, are increasingly encountering complex and cross-cutting issues such as economic and financial volatility, internal and external conflicts, growing social tensions, adverse demographic trends, climate change vulnerabilities, weak regulatory regimes, huge infrastructure and service delivery gaps, state and elite capturing and sustaining rule of law. Faced with growing criticism of infectiveness of state institutions undermining country’s economic, social and political development because of weakening capacity of public officials to pace up with emerging challenges, there is a renewed interest in reforming the governance and reforming the civil service.